PAHs and hopanes in the surface sediments of Qatar coast and their ecological risks: Comparison with regional and global coastal regions - Samah Dib (22046891) (2024)
The distribution, characteristics, sources and ecological risks of polycyclic aromatic hydrocarbons (PAHs) and hopanes in the surface sediments collected along the Qatar coast were investigated. Concentration of ∑14PAHs and hopanes ranged between 0.076 and 7.04 ng g−1 (mean: 2.60 ng g−1), 100 and 700 ng g−1 (mean: 205 ng g−1), respectively. Sediment samples were dominated by high molecular weight PAHs composition (4–6 rings). Diagnostic ratios of PAH concentrations showed both petrogenic and pyrogenic origins of PAHs, with a higher percentage of pyrogenic sources. The ecological risk levels of PAHs were estimated using sediment quality guidelines (SQG), mean probable effect level quotient values (PEL-Q), carcinogenic toxic equivalent quantity (TEQ), and risk quotient (RQ) evaluation methods. The calculated TEQ values (0.00012–0.85 ng g−1) were lesser than those in other locations around the globe, and were also within the safe level (600 ng g−1) suggested by the Canadian soil quality guidelines. Other Information Published in: Marine Pollution Bulletin License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.marpolbul.2024.116494